1981
DOI: 10.1136/gut.22.2.130
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of the diagnostic accuracy of liver ultrasonography.

Abstract: SUMMARY Liver ultrasound was prospectively evaluated in 104 subjects who underwent liver biopsy, including 24 patients without evidence of liver disease (controls), and 80 with a broad spectrum of liver pathology. Ultrasonography was very specific (100%) and moderately sensitive (70%) in the detection of liver pathology, and hepatic neoplasms, steatosis, and fibrosis were detected by ultrasound in 80%, 80%, and 67% of cases respectively. In addition, ultrasonography diagnosed other pathologies-mainly biliary t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
1
4

Year Published

1985
1985
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(47 citation statements)
references
References 14 publications
2
40
1
4
Order By: Relevance
“…4 The major factor that has inhibited decision making based on ultrasound findings in patients with parenchymal liver disease is the doubt about the accuracy of scanning when performed in the routine clinical setting. Furthermore, the reported accuracy in selected groups of patients in both retrospective and prospective studies has varied greatly, particularly for patients with fatty infiltration, with sensitivities ranging from 9% in patients with alcoholic liver disease6 to 80% in patients with unselected liver 7 disease.…”
Section: Introductionmentioning
confidence: 99%
“…4 The major factor that has inhibited decision making based on ultrasound findings in patients with parenchymal liver disease is the doubt about the accuracy of scanning when performed in the routine clinical setting. Furthermore, the reported accuracy in selected groups of patients in both retrospective and prospective studies has varied greatly, particularly for patients with fatty infiltration, with sensitivities ranging from 9% in patients with alcoholic liver disease6 to 80% in patients with unselected liver 7 disease.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is difficult to distinguish liver fibrosis from hepatosteatosis [17,18,21] . In studies, the sensitivity and specificity of US in detecting hepatosteatosis have been found to be 60%-94% and 84%-95%, respectively [16,18,22,23] . Hamaguchi et al [24] reported that US has a high sensitivity (91.7%) and specificity (100%) for fatty liver detection.…”
Section: Usmentioning
confidence: 99%
“…LS has been recognized by a BLP in 1979 [26]. Some authors consider this pattern as highly correlated with LS [6,7,9,10,12,13], especially if associated with a posterior beam attenuation and/or skip areas [10]. Nevertheless, other authors think that BLP might also indicate liver fibrosis [13,[17][18][19][20].…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the ability of ultrasound to evaluate the presence and degree of LS remains debatable. In fact, although some authors have shown that the bright liver echo pattern (BLP) is strongly correlated with the diagnosis of hepatic steatosis [6][7][8][9][10][11][12][13], other authors think that this pattern is non-specific because the liver echogenicity on ultrasonography also increases with liver fibrosis [14][15][16][17][18][19][20]. Recently, the simultaneous presence of BLP, posterior attenuation, and/or areas with different patterns of fat infiltration (so-called skip areas) around gallbladder or near the portal vein [21] have been identified as distinctive signs of steatosis involving a number of hepatocytes in a microscopic field [30 % [11].…”
Section: Introductionmentioning
confidence: 99%